Immunomodulatory effect of betulin and its derivatives on IL-6 expression in colorectal cancer cell lines and molecular docking insights - Madej, Marcel; Halama, Adrianna; Chrobak, Elwira; Bębenek, Ewa; Gola, Joanna Magdalena (Frontiers in Molecular Biosciences, 2025)
PurposeThis study investigated the immunomodulatory and therapeutic potential of betulin and its derivatives (EB5 and ECH147) in colorectal cancer (CRC), focusing on their effects on IL-6 expression at the molecular level and their possible application as diagnostic and therapeutic tools.MethodsHuman CRC cell lines (HT-29, RKO, SW1116) and normal colonocytes (CCD-841CoN) were treated with betulin, EB5, ECH147, cisplatin, and 5-fluorouracil (10 μg/mL) for 2, 8, and 24 h. IL-6 mRNA levels were measured by RT-qPCR in real time, and IL-6 protein was quantified using a proximity ligation immunoassay. Molecular docking was performed using IL-6 structure (PDB ID: 1ALU). Statistical significance was evaluated using Kruskal–Wallis and post hoc rank tests.ResultsIL-6 expression was undetectable in HT-29 and RKO cells, both harboring the BRAFV600E mutation. ECH147 and EB5 derivatives significantly decreased IL-6 mRNA and protein levels in SW1116 and CCD-841CoN cells at 8 and 24 h. Molecular docking analysis revealed that ECH147 formed a stable hydrogen bond, suggesting direct binding.ConclusionStructural modification of betulin enhances its molecular therapeutic activity, with phosphonate derivative ECH147 showing the strongest decrease in IL-6 levels. These findings suggest that IL-6 downregulation can serve as a molecular biomarker for drug efficacy, while ECH147 represents a promising candidate for targeted molecular therapy in CRC. This dual diagnostic–therapeutic approach highlights the potential of betulin derivatives in advancing precision medicine for IL-6–mediated pathways.